Effectiveness of the Kemendikbudristek Teaching Campus Program at UPT SPF SD Inpres Kalangtubung I - Nurul Hidayah Zainal; Syahrul Zainal; Purnamawati (PT. Global Research Collaboration, 2026)
This study is a program evaluation aimed at describing and analyzing the effectiveness of the implementation of the Ministry of Education, Culture, Research, and Technology’s Teaching Campus Program at UPT SPF SD Inpres Kalangtubung I. The study employed the CIPP evaluation model, examining the context, input, process, and product aspects of program implementation. Data were collected through interviews, observations, and documentation, with informants consisting of ten individuals, including school representatives and students assigned to the Teaching Campus program. The evaluation results indicate that, from a contextual perspective, the program was implemented in accordance with Regulation of the Minister of Education and Culture Number 22 of 2020, guided by the Teaching Campus Guidebook issued by the Directorate General of Higher Education, Research, and Technology, and aligned with both school needs and program objectives. In terms of input, program priorities were appropriately aligned with school needs, and the competencies of the student implementation team particularly in communication and social interaction supported effective execution. From a process perspective, program activities were carried out according to the established collaboration action plan, supported by students’ adaptability, resilience, and solution-oriented approaches to challenges encountered. From a product perspective, the Teaching Campus program achieved its intended objectives and generated positive impacts for both the target school and participating students. Overall, the findings indicate that the Teaching Campus Program at UPT SPF SD Inpres Kalangtubung I was implemented effectively.